2011
DOI: 10.1111/j.1365-2648.2011.05611.x
|View full text |Cite
|
Sign up to set email alerts
|

Contextual factors influencing success or failure of emergency department interventions for cognitively impaired older people: a scoping and integrative review

Abstract: Although the prevalence and incidence of cognitive impairment is recognized, appropriate interventions and programmatic responses remain elusive. Quality improvements require more thorough examination of emergency department context to identify modifiable influencing factors that are transferable across settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 84 publications
0
35
0
1
Order By: Relevance
“…However, the study excluded patients with clinical needs for specialist services, such as surgery or stroke units. A scoping review of interventions for cognitively impaired older people in emergency departments found no evaluations of organisational or system level interventions and little evidence of appropriate interventions [61]. We found no evaluations of interventions aimed specifically at our three target comorbidities, although a retrospective analysis of stroke patients suggested that cognitively impaired patients benefit from admission to an acute rehabilitation stroke unit [63].…”
Section: Models Of Care For Older People With Cognitive Impairmentmentioning
confidence: 82%
“…However, the study excluded patients with clinical needs for specialist services, such as surgery or stroke units. A scoping review of interventions for cognitively impaired older people in emergency departments found no evaluations of organisational or system level interventions and little evidence of appropriate interventions [61]. We found no evaluations of interventions aimed specifically at our three target comorbidities, although a retrospective analysis of stroke patients suggested that cognitively impaired patients benefit from admission to an acute rehabilitation stroke unit [63].…”
Section: Models Of Care For Older People With Cognitive Impairmentmentioning
confidence: 82%
“…124 We found no evaluations of interventions aimed specifically at our three target comorbidities, although a retrospective analysis of stroke patients suggested that cognitively impaired patients benefit from admission to an acute rehabilitation stroke unit. 126 …”
Section: Results Of the Scoping Reviewmentioning
confidence: 99%
“…Best practice potentials for the care of this vulnerable population in the ED setting, some of which having been proposed by other authors, 3,12,32 are presented in Box 1. In ED, there was geriatric input in one patient only, while a geriatric assessment team would have accepted care of 108 patients who were subsequently admitted to the acute care setting.…”
Section: Improving Patient Care and Outcomesmentioning
confidence: 99%
“…[11][12][13] Several recommendations, targeting ED's physical layout, modifications of care delivery, and staff education, have been reported to improve the ED experience and outcomes of seniors with CI and their families. 3,11,14 Establishing or refining specific ED services and robust care delivery protocols relevant to the clinical care of this at-risk ED population first requires a good understanding of their presenting features and needs.…”
Section: Introductionmentioning
confidence: 99%